Human chromosome aberrations induced in vitro by Paracoccidioides brasiliensis glycoproteic component (GP 43) - Villalba Freire-Maia, Dertia [UNESP]; Aparecida Spadotto Balarin, Marly; José Mendes-Giannini, Maria [UNESP] (Elsevier, 1997)
The in vitro cytogenetic effects of the 43-kDa molecular mass exocellular glycoproteic component (GP 43) from Paracoccidioides brasiliensis were studied in cultures from human lymphocytes. The sample included 10 healthy, white, non-smoking, non-related males (mean age of 31.3 ± 8.2 years). Besides the control, three concentrations of GP 43 (0.125, 1.25 and 5 μg/ml) were used. In each group, around 1000 cells were examined in search of chromosome aberrations, and 30,000 metaphases were analysed for the determination of the Mitotic Index. The authors conclude that GP 43 most probably causes inhibition of the cell cycle and aneugenic and clastogenic effects.
Keywords: Chromosome aberration; Cytogenetics; GP 43; Mitotic index; Mutagenesis; Paracoccidioides brasiliensis; Paracoccidioidomycosis; glycoprotein; adult; chromosome aberration; controlled study; cytogenetics; human; human cell; in vitro study; lymphocyte culture; male; mutagenesis; normal human; paracoccidioides brasiliensis; priority journal; structural chromosome aberration; Adult; Aneuploidy; Antigens, Fungal; Cells, Cultured; Chromosome Aberrations; Fungal Proteins; Glycoproteins; Humans; Lymphocytes; Male; Metaphase; Mitotic Index; Mutagenicity Tests; Oligosaccharides